Impact of River Infrastructure on Sediment Distribution to Maintain Reservoir Lifespan: A Case of the Bili-Bili Reservoir, Jeneberang Basin, Indonesia - Hasnawi, Mursyid Hasnawi; Ritnawati; Mahyuddin; La Ode Agisaqma; Muhammad Subri (Universitas Negeri Semarang, 2025)
This study investigates the impact of river infrastructure on sediment distribution in the Bili-Bili Reservoir. Bathymetric data obtained using an echo-sounding sonar system were processed with Surfer 14 to analyze reservoir bottom morphology, storage capacity, and sediment accumulation. Hydrological modeling with NRECA calibration was combined with field measurements to estimate sediment inflow and storage loss. Results show cumulative sedimentation increased by 42% (1997–2005), 33% (2005–2011), and 25% (2011–2017), with a peak deposition of 21.74 × 10⁶ m³ in 2005. Following the construction of sabo dams, consolidation dams, and check dams in 2011, sedimentation rates decreased by 57% relative to 2005. Reservoir capacity declined from 365 × 10⁶ m³ in 1997 to 264 × 10⁶ m³ in 2017, reducing the effective service life by approximately 6.5 years. The remaining lifespan of the reservoir in 2017 was 24 years and 4 months, compared to the original design life. These findings emphasize that periodic dredging (every four years), monthly sediment removal at the consolidation dam, and sediment trapping in the Jeneberang watershed are essential to sustain reservoir performance.